Comparative analysis of the strength characteristics of light polymerization polymers for dental restoration using the acoustic emission method. Fractographic studies of the surface and fractures of the samples: part two - Kukhta В. С.; Makeyev В. Ф.; Kyrmanov О. С.; Skalsky В. Р.; Stankievych О. М. (Actual Dentistry, 2022)
Purpose. Comparative analysis of the strength of hybrid restoration composites of light polymerization during their local load using the phenomenon of acoustic emission and fractographic studies of fracture samples. Materials and methods. For comparative studies, hybrid dental composites of domestic and foreign production were selected: Latelux (Latus, Ukraine), Tetric N-Ceram (Ivoclar Vivadent, Liechtenstein), Charisma Classic (Kulzer, Germany). Disc samples 13 mm in diameter and 5 mm thick, which were made in a specially designed form, were used for testing. The samples were loaded on an SVR-5 installation using a ball indenter with a speed of its movement of 0.002 mm/s until the samples were destroyed. During the experiments, acoustic emission information was simultaneously recorded using the SKOP-8 measuring system. Electron microscopic studies of materials were performed using a scanning electron microscope (SEM) ZEISS EVO 40XVP. Results. Under loading by local compression, mixed types of fracture occur in the dental composites under study, with the difference that plastic deformation is partially less pronounced in the Charisma Classic composite and more radial macrocracks propagate in Tetric N-Ceram and Charisma Classic. Conclusions. Comparison of the sizes of chips in different materials, which were formed as a result of the propagation of conical cracks, makes it possible to make the result that during the local compression load of the Latelux composite new fracture surfaces were formed, much smaller than in the other two materials. Their formation was accompanied by AE signals with significantly lower amplitudes and then energy than in the Tetric N-Ceram and Charisma Classic composites.